Factors that cause the increase of pneumonia in Indonesia - Pestaria Saragih; Vita Eskana Sihombing; Indah Boni Yolanda Pardede (AMCA, 2022)
Lower respiratory tract infections are still a major problem in the health sector. According to the World Health Organization (WHO), lower respiratory tract infections are the most common cause of death in the world. Pneumonia is an inflammation of the lungs that causes pain when breathing and limited oxygen intake. Pneumonia can be spread in a number of ways, including when you cough and sneeze. The type of research used in this study is descriptive, to find out what factors are causing the increase in pneumonia in Indonesia. From the data conducted by reviewing various journals, it was found that there are 3 factors causing the increase in pneumonia in Indonesia, namely Air Pollution, Air Humidity, and Lifestyle. Various factors that can cause pneumonia are air pollution, humidity, and lifestyle